(NmUZYKA (B1 (NKLASS(B.s (NKNIGA DLQ OB]EOBRAZOWATELXNOJ [KOLY(B.s - (Nm(B.(NrUMER(B.s; (Nk(B.(NgRI]ENKOs (NDRUGOJ AWTORs ((NmOSKWAs (NmUZYKAs, 1979)
(NuZNATX NOWOE O MUZYKE WAM POMOVET \TA KNIGA(B.s
Keywords: (NmUZYKALXNOE OBROZAWANIEs